2000
DOI: 10.1302/0301-620x.82b3.10465
|View full text |Cite
|
Sign up to set email alerts
|

Cemented total hip arthroplasty with autogenous acetabular bone grafting for hips with developmental dysplasia in adults

Abstract: We carried out primary cemented total hip arthroplasty (THA) on 25 hips in 21 patients with developmental dysplasia of the hip, using autogenous acetabular bone grafts. The socket was placed at the level of the true acetabulum and bone from the femoral neck was used as graft. Five hips were excluded, leaving 20 which were followed up for a mean of 12.9 years (10 to 18). The mean modified Merle d'Aubigné and Postel functional scores were 5.6 for pain, 4.3 for mobility and 4.2 for range of movement. Radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…6,47 This may have been because of the difficulty in revascularising and remodelling such large grafts, and the load they carried during this process. However, in series where smaller grafts were used, 29,30,[48][49][50][51][52] as in this study, results have been good. We accept that in this study group most patients (85 hips) had only minor dysplasia.…”
Section: Discussionmentioning
confidence: 63%
“…6,47 This may have been because of the difficulty in revascularising and remodelling such large grafts, and the load they carried during this process. However, in series where smaller grafts were used, 29,30,[48][49][50][51][52] as in this study, results have been good. We accept that in this study group most patients (85 hips) had only minor dysplasia.…”
Section: Discussionmentioning
confidence: 63%
“…The percentage of the acetabular component covered by the bone was measured using the horizontal distance of the acetabular component covered by the bone (b) and the horizontal distance between the most medial edge and the lateral point of the acetabular component (a) [11]. Coverage percentage = b/a × 100% (Fig.…”
Section: Radiographic Follow-upmentioning
confidence: 99%
“…A significant factor in the outcome of these procedures is the achievement of short term stability prior to incorporation of MCB into the host skeleton ensuring long term stability of the prosthetic components (Iida et al, 2000;Inao and Matsuno, 2000). In the acetabular construct it has been found that excessive migration and rotation of the acetabular cup can occur soon after operation due to instability initiating in the MCB bed (Ornstein et al, 1999;Phillips et al, 2004).…”
Section: Introductionmentioning
confidence: 99%